Effect of naturally derived surgical hemostatic materials on the proliferation of A549 human lung adenocarcinoma cells. (March 2022) - Lü, Wei-Dong; Liu, Yi-Zhi; Yang, Yan-Qi; Liu, Zhi-Gang; Zhao, Kun; Lu, Jian-Rong; Lei, Guang-Yan; Wang, Yi-Yu; Cai, Lin; Sun, Rui-Fang
Abstract: Hemostatic materials are generally applied in surgical operations for cancer, but their effects on the growth and recurrence of tumors are unclear. Herein, three commonly used naturally derived hemostatic materials, gelatin sponge, Surgicel (oxidized regenerated cellulose), and biopaper (mixture of sodium hyaluronate and carboxymethyl chitosan), were cocultured with A549 human lung adenocarcinoma cells in vitro . Furthermore, the performance of hemostatic materials and the tumorigenicity of the materials with A549 ​cells were observed after subcutaneous implantation into BALB/c mice. The in vitro results showed that biopaper was dissolved quickly, with the highest cell numbers at 2 and 4 days of culture. Gelatin sponges retained their structure and elicited the least cell infiltration during the 2- to 10-day culture. Surgicel partially dissolved and supported cell growth over time. The in vivo results showed that biopaper degraded rapidly and elicited an acute Th1 lymphocyte reaction at 3 days after implantation, which was decreased at 7 days after implantation. The gelatin sponge resisted degradation and evoked a hybrid M1/M2 macrophage reaction at 7–21 days after implantation, and a protumor M2d subset was confirmed. Surgicel resisted early degradation and caused obvious antitumor M2a macrophage reactions. Mice subjected to subcutaneous implantation of A549 ​cells and hemostatic materials in the gelatin sponge group had the largest tumor volumes and the shortest overall survival (OS), while the Surgicel and the biopaper group had the smallest volumes and the longest OS. Therefore, although gelatin sponges exhibited cytotoxicity to A549 ​cells in vitro, they promoted the growth of A549 ​cells in vivo, which was related to chronic M2d macrophage reaction. Surgicel and biopaper inhibited A549 ​cell growth in vivo, which is associated with chronic M2a macrophage reaction or acute Th1 lymphocyte reaction. Graphical abstract: Image 1 Highlights: The gelatin sponge, Surgicel and biopaper had different effects on A549 ​cell growth and proliferation . Biopaper degraded rapidly in vivo and elicited an antitumor Th1 lymphocyte reaction at acute inflammatory phase. The gelatin sponge resisted degradation and evoked a protumor M2d macrophage reactions. Surgicel resisted early degradation and caused obvious antitumor M2a macrophage reactions.